Academic stress among university students: A quantitative study of generation Y and Z’s perception - Ramachandiran, Malarvili; Dhanapal, Saroja (Universiti Putra Malaysia, 2018)
Concerns on academic-related stress among students in institutions of higher learning are widespread. Pursuing tertiary education is said to be stressful as students pass through the process of adapting to new educational and social environments. Past literature has highlighted that common academic stressors include family-related pressures, scholarship requirements, financial burdens, competition in class and course-related stress. These stressors trigger physical and psychological issues resulting in lack of energy, loss of appetite, headaches, sleep problems or gastrointestinal problems. Although studies have been done on common stressors in universities/colleges, perceptions of what are considered academic stressors from the Generation Y and Z perspectives using the Perceived Stress Test (PSS) have not been carried out in the Malaysian context. Thus, this quantitative study aims to identify the perceptions of Gen Y and Z (18-25 years old) students to identify factors attributing to stress and their effects. The findings show that 88% of the respondents confirmed that studies are the main cause of their stress, while 78% admitted facing a moderate stress level and out of this, 36% had BMI that fell in the overweight/ obese category. Further, the study indicates that 54% experienced sleeping disorders. It is hoped that the findings will add to the understanding of the stress levels among Generation Y and Z to enable policy-makers and university/college management teams to strategise actions to alleviate issues arising from academic stress among students.